Numerical simulation of the breaching of an earth dam due to overtopping - Huynh Cong Hoai; Tawatchai Tingsanchali; Suphat Vongvisessomjai; Tanaka, Hitoshi; Tran Thuc; The Government of Australia (Bangkok : Asian Institute of Technology, 1992)
A numerical model is developed consisting of a flow model and a morphological model to simulate the erosion process on the crest and along the downstream surface of a breaching earth dam due to flow overtopping. The water surface profile over the dam downstream surf ace is solved by a step method and the scour profile of the dam downstream surface is solved by using an explicit finite difference technique of the modified Lax-Scheme. The experiments with the model dam made of sand are carried out in laboratory flume. Different discharges are used in two runs (runt and run2). In each run, the scour profile of dam, the overtopping discharge, the water surf ace level at upstream of dam and the water surf ace profile over the dam crest and along downstream dam surface are measured. The flow model and the morphological model are calibrated and verified with the experimental data of runt and run2 respectively. The numerical model is computed with various sediment transport formulae namely Einstein-Brown, modified Meyer-Peter and Muller, Engelund-Hansen and Van Rijn. It is found that the modified Meyer-Peter and Muller (MPM) formula for steep bed slope yields the best computed results compared with the experimental data. The agreement are found to be very satisfactory. Sensitivity analysis is made to study the influence of bed load transport formula, Manning roughness coefficient, slope and numerical scheme on the computed results. It is found that the sediment transport formula, the bed slope and the Manning n are the important hydraulic physical parameter that control the accuracy of the results. Moreover, the numerical parameter namely the space weighting factor (a) has a significant influence on the computed results. A computer program written in Fortran77 language with a capacity to display the variation of the scouring of bed profile with time is provided.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1992
Keywords: Earth dams -- Mathematical models